Multimodel assessment of water budget in Indian sub-continental river basins - Kushwaha, Anuj Prakash; Tiwari, Amar Deep; Dangar, Swarup; Shah, Harsh; Mahto, Shanti Shwarup; Mishra, Vimal (Journal of hydrology (Amsterdam), 2021)
[Display omitted] •Water budget was estimated in the Indian sub-continental river basins.•Multimodel ensemble mean performs better than the individual models.•Transboundary river basins (Brahmaputra, Ganga, and Indus) have the highest water yield.•West coast, Brahmaputra, and Brahmani are the three wettest river basins. Estimation of the water budget is essential for water resources and environmental management. However, a reliable assessment of the water budget and water yield for the Indian sub-continental river basins has been lacking. We used 0.25° gridded meteorological observations and five hydrological models to construct water budget estimates for the Indian sub-continental river basins for the 1951–2016 period. The hydrological models (i.e. VIC, CLM, Noah-MP, H08, and CWatM) were calibrated against observed streamflow and evaluated for evapotranspiration (ET) and soil moisture. Considerable uncertainty in the water budget components (ET and total runoff) was found due to the process representation and parameterization of hydrological models. Multimodel ensemble mean of the five hydrological models performed better than individual models for most basins for water budget components. West coast, Brahmaputra, and Brahmani are the three wettest river basins. At the same time, Sabarmati, Indus, and Pennar are the three driest basins in terms of mean annual precipitation in the Indian sub-continent. The three transboundary river basins (Brahmaputra, Ganga, and Indus) have the highest water yield of 731.9 (±50.2), 582.4 (±89.4), and 231.1(±71) km3, respectively. The Budyko framework showed that only two basins (West Coast and the Brahmaputra) over the Indian sub-continent fall under the energy-limited (relatively lower atmospheric water demands) conditions. In comparison, the other sixteen river basins are in water-limited (higher atmospheric water demands) condition. Our findings have implications for water resources planning and management in one of the world's most populated regions.